Hippocampus and amygdala volumes in patients with vaginismus - Atmaca, Murad; Baykara, Sema; Ozer, Omer; Korkmaz, Sevda; Akaslan, Unsal; Yildirim, Hanefi (Baishideng Publishing Group Inc, 2016)
AIM: To compare hippocampus and amygdala volumes of patients with vaginismus with those of healthy control subjects. METHODS: Magnetic resonance imaging was performed on ten patients with vaginismus and ten control subjects matched for age and gender. Volumes of the hippocampus and amygdala were blindly measured. RESULTS: We found that the mean right amygdala volume of patients with vaginismus were smaller than that of the healthy controls. With regard to hippocampus volumes, the mean left and right hippocampus volumes were smaller than those of the healthy controls. CONCLUSION: Our present findings suggest that there have been hippocampus and amygdala structural abnormalities in patients with vaginismus. These changes provide the notion that vaginismus may be a fear-related condition.
Keywords: Vaginismus; Hippocampus; Amygdala; Volumes; Patients